Co3O4 Nanoparticles Supported on Mesoporous Carbon for Selective Transfer Hydrogenation of α, β‐Unsaturated Aldehydes. (28th July 2016) - Wang, Guang‐Hui; Deng, Xiaohui; Gu, Dong; Chen, Kun; Tüysüz, Harun; Spliethoff, Bernd; Bongard, Hans‐Josef; Weidenthaler, Claudia; Schmidt, Wolfgang; Schüth, Ferdi
Abstract: A simple and scalable method for synthesizing Co3 O4 nanoparticles supported on the framework of mesoporous carbon (MC) was developed. Benefiting from an ion‐exchange process during the preparation, the cobalt precursor is introduced into a mesostructured polymer framework that results in Co3 O4 nanoparticles (ca. 3 nm) supported on MC (Co3 O4 /MC) with narrow particle size distribution and homogeneous dispersion after simple reduction/pyrolysis and mild oxidation steps. The as‐obtained Co3 O4 /MC is a highly efficient catalyst for transfer hydrogenation of α, β‐unsaturated aldehydes. Selectivities towards unsaturated alcohols are always higher than 95 % at full conversion. In addition, the Co3 O4 /MC shows high stability under the reaction conditions, it can be recycled at least six times without loss of activity.